2013
DOI: 10.1002/cjce.21869
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on the effect of conical geometry on flow behaviours in spouted beds

Abstract: Evaluation on the effect of conical section geometry on the gas–solid flow behaviours in conical–cylindrical spouted beds were carried out by three‐dimensional computational fluid dynamics (CFD) coupling with two‐fluid model (TFM). The simulations were implemented in seven columns with their conical angles ranging from 30° to 180°. The solid flow pattern, particle velocity, voidage, fountain height and the spout diameter were investigated. It was found that unstable spouting would occur when the conical angle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…They showed that conical angle in spouted beds is a critical parameter in appearance of unstable spouting. Liu et al [48] also showed that unstable spouting would occur when the conical angle is less than 30°by CFD tool.…”
Section: Particle Velocity Distributionmentioning
confidence: 95%
“…They showed that conical angle in spouted beds is a critical parameter in appearance of unstable spouting. Liu et al [48] also showed that unstable spouting would occur when the conical angle is less than 30°by CFD tool.…”
Section: Particle Velocity Distributionmentioning
confidence: 95%
“…Liu and colleagues [236] assessed the influence of the conical base angle on the spouting regime; they found out that the spouting was unstable for angles inferior to 30 • , and that the fountain height and spout diameter had a maximum angle of 105 • . Also, the velocity of particles in the annulus kept increasing as the angle was further increased.…”
Section: Tfm Applied To Auxiliary Devicesmentioning
confidence: 99%
“…Gidaspow [154] 17 [25,91,[204][205][206][208][209][210]213,218,220,222,226,228,229,234,235] Syamlal-O'Brien [158] 14 [89,90,92,114,203,207,214,215,224,225,[230][231][232]236 Turbulence was not extensively discussed in most works and when considered, the k-ε turbulence model [239] was mostly employed. As it can be seen in Table 9, almost half of the works did not include a turbulence model.…”
Section: Drag Law Number Of Occurrences Referencesmentioning
confidence: 99%
“…The effect of IA of the spouted bed was previously evaluated on the flow behavior , . In the current simulation, the effect of IA on temperature evolution in a spouted bed is further explored.…”
Section: Resultsmentioning
confidence: 99%